PENGARUH PENGHARGAAN (REWARD) DAN MOTIVASI BERPRESTASI TERHADAP PRESTASI KERJA GURU SMA NEGERI DI KABUPATEN SUKABUMI - Siti Nurpina (Jurnal Manajemen Pendidikan, 2016)
This study aims to determine the effect of (1) rewrad, (2) achievement motivation, (3) performance of teachers working SMAN Negeri District of SukabumI. In the data analysis, this study used a survey method using a causal analysis technique Strip . This study used a sample of 150 teachers in six high schools in District of Sukabumi are selected using Slovin formula.The results showed that : first, there are positive influence between the rewrad and performance of teachers in schools . Secondly, there is a positive effect between achievement motivation and performance of teachers in schools. Third, there is a positive effect between the reward and achievement motivatioan of teachers in schools.